Evaluasi Kinerja Struktur Gedung Bertingkat dengan Metode Analisis Pushover (Studi Kasus: Gedung 6 Rumah Sakit Pendidikan Perguruan Tinggi Negeri (RSPTN) Universitas Lampung) - Mustofa, Ragat Aji; Bayzoni, Bayzoni; Husni, Hasti Riakara; Isneini, Mohd (Universitas Lampung, 2024)
The high potential for earthquake in Indonesia encourages the design of buildings to be resistant towards earthquake vibrations. The level of vulnerability to lateral forces, especially earthquake shocks, is closely related to the height of the building. Therefore, the design of multi-storey building structures must be designed by analyzing earhquake loads with the aim of preventing the building from collapsing and reducing the number of fatalities due to earthquakes. This research takes a case study at Building 6th of the State University Education Hospital of University of Lampung using a performance-based seismic design approach, which involves the use of non linear pushover analysis techniques based on ATC-40 (capacity spectrum method) and FEMA-356 (displacement coefficient method). The result of the pushover analysis are capacity curves, building displacement targets, building collapse schemes, and result of building performance evaluations against earthquake loads based on ATC-40 and FEMA-356 regulations. The analysis result show that the level of building performance in the x-direction and y-direction with the maximum total drift ratio parameter based on ATC-40 and FEMA-356 is Immediate Occupancy, so it can be concluded that the building is still able to withstand when an earthquake occurs and the risk of human loss is very small.